Usability Evaluation of Lecturer Information Systems Using Sirius Framework and Moscow Technique - Ramayasa, I Putu; Candrawibawa, I Gede Angga (Scientific Journal of Informatics, 2021)
Purpose: This study aims to evaluation of the SID ITB STIKOM Bali usability was carried out using used framework and the Moscow technique, where until now there has never been an evaluation of the usability of SID, causing the relevant stakeholders not to know the usefulness of the system and not knowing the improvements that need to be made to the SID system. Methods: The method chosen in this study is literature study and observation, SID system analysis, distribution and processing questionnaire data, data analysis, and concluding. Result: The result of this study is the global usability value for SID based on ten aspects of the Sirius framework usability and recommendations for improving the SID STIKOM Bali system based on the Moscow Technique ranking. Novelty: This research's novelty can be a reference material for stakeholders in determining policies related to improving the SID system at ITB STIKOM Bali.